Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.1 - Simplifying Rational Expressions - Exercise Set: 67


Answer is correct. $\frac{x+7}{-5x-1}$

Work Step by Step

Answer is correct because: $\frac{7-34x-5x^{2}}{25x^{2}-1}$= $\frac{7+x-35x-5x^{2}}{25x^{2}-1}$= $\frac{7+x-35x-5x^{2}}{25x^{2}-1}$= $\frac{1(7+x)-5x(7+x)}{(5x)^{2}-1^{2}}$= $\frac{1(7+x)-5x(7+x)}{(5x)^{2}-1^{2}}$= $\frac{(1-5x)(7+x)}{(5x+1)(5x-1)}$= $\frac{(1-5x)(7+x)}{(5x+1)(-1)(1-5x)}$= $\frac{(7+x)}{(5x+1)(-1)}$= $\frac{(x+7)}{-5x-1}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.